Non-occupational HIV exposure and post exposure prophylaxis : knowledge and practice among police and prison service personnel in Blantyre, Malawi - Soko, Douglas (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.